2014
DOI: 10.1021/ie503216p
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Chemical Surface Modification for the Fabrication of PEBA/SiO2 Nanocomposite Membranes To Separate CO2 from Syngas and Natural Gas Streams

Abstract: 9In this work, a novel chemical modification is introduced to fabricate poly (ether block 10 amide)/silica, (PEBA/SiO2), nanocomposite membranes for separation of CO 2 from syngas and 11 natural gas streams. Cis-9-octadecenoic acid (OA) was utilized for surface modification of the 12 nanoparticles to restrict their agglomeration within the polymeric matrix. To our best knowledge, 13 there is no evidence about application of this modifier agent for fabrication of nanocomposite 14 membranes. Separation performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(31 citation statements)
references
References 51 publications
(71 reference statements)
0
31
0
Order By: Relevance
“…The result of using the modified ZnO nanoparticles showed that they could be kept dispersed for 24 h. This time was enough to avoid precipitation of the modified nanoparticles in the polymer matrix during the nanocomposite membranes synthesis. Ghadimi et al [31] also employed OA for surface modification of silica in order to incorporate it into PEBAX-1657.…”
Section: Synthesis Of Membranesmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of using the modified ZnO nanoparticles showed that they could be kept dispersed for 24 h. This time was enough to avoid precipitation of the modified nanoparticles in the polymer matrix during the nanocomposite membranes synthesis. Ghadimi et al [31] also employed OA for surface modification of silica in order to incorporate it into PEBAX-1657.…”
Section: Synthesis Of Membranesmentioning
confidence: 99%
“…In addition, mole fraction of components in the feed and the permeate streams are indicated by x i and y i , respectively. It should be noted that, in the case of pure gas experiments, x i and y i are considered equal to 1 [31] . It is also necessary to mention that all the experiments at different conditions were repeated three times for each sample and the recorded permeability values are on average.…”
Section: Gas Adsorption and Permeation Measurementmentioning
confidence: 99%
“…[27] prepared chemically modified SiO 2 -PEBAX-1657 composite membranes to improve the separation performances of PEBAX-1657. They found higher permeations for CO 2 and lower values for CH 4 , and hence, the greatly enhanced ideal selectivity for CO 2 /CH 4 separation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8,9 ] Most recently, poly (ethylene oxide) (PEO)-based polymeric membranes have attracted signifi cant scientifi c interest for H 2 purifi cation and CO 2 capture, due to the dipole-quadrupole interaction between CO 2 -philic units of ethylene oxide (EO) and CO 2 molecules. [ 10,11 ] However, the high crystalline nature of PEO linear chains endows the membranes with very low gas permeability (about 12 Barrer for CO 2 , 1 Barrer = 10 −10 cm 3 (STP) cm cm −2 s −1 cmHg −1 ) attributed to the impermeability of the continuous crystalline regions.…”
mentioning
confidence: 99%